Interpreting ALMA non-detections of JWST super-early galaxies. Issue 1 (2nd January 2023) - Kohandel, M; Ferrara, A; Pallottini, A; Vallini, L; Sommovigo, L; Ziparo, F
ABSTRACT: Recent attempts to detect [O iii ] 88 μ m emission from super-early ( z > 10) galaxy candidates observed by JWST have been unsuccessful. Non-detections can be either due to wrong photometric redshifts or to the faintness of the line in such early systems. By using zoom-in simulations, we show that if redshifts of these galaxies are confirmed, they are faint and mostly fall below the local metal-poor [O III]-SFR relation as a result of their low ionization parameter, U ion ≲ 10 −3 . Such low U ion values are found in galaxies that are in an early assembly stage, and whose stars are still embedded in high-density natal clouds. However, the most luminous galaxy in our sample (log[L_[O III]/L_] = 8.4, U ion ≈ 0.1) could be detected by ALMA in only 2.8 h.